2007
DOI: 10.1007/bf03033414
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of exam performance in Web and lecture courses

Abstract: ~sP~cFIRST OBJECTIVE OF THIS RESEARCH was to come the demographic and academic profiles of introductory iology students who completed Web-based courses (n = 62) to those who completed traditional lecture-based courses (n = 77). The second objective was to determine the extent to which demographic variables (age, gender, and race), academic variables (high school grade point average, and verbal and quantitative Scholastic Assessment Test scores) differentially predicted exam performance in the two learning envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…However, self‐study time and personality mattered little to student performance in Mode C. In contrast, female, older and high‐achieving students tended to perform better in teacher‐led in‐class instruction. While maturity and prior academic achievement are often associated with superior learning performance (Brallier, Palm, & Gilbert, ; Muse, ), the relevance of gender is still inconclusive in the literature. Therefore, this finding in the present study can provide insight into gender differences in the flipped classroom.…”
Section: Discussionmentioning
confidence: 99%
“…However, self‐study time and personality mattered little to student performance in Mode C. In contrast, female, older and high‐achieving students tended to perform better in teacher‐led in‐class instruction. While maturity and prior academic achievement are often associated with superior learning performance (Brallier, Palm, & Gilbert, ; Muse, ), the relevance of gender is still inconclusive in the literature. Therefore, this finding in the present study can provide insight into gender differences in the flipped classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been carried out with the belief that the absence of monitoring in the NPR method increases the probability of cheating, which produces higher grades than the PFTF method; however, no consensus has been reached. Ardid et al (2015), Brallier and Palm (2015), Carstairs and Myors (2009), Fask et al (2014), Harmon and Lambrinos (2008) and Schultz et al (2007) find that there are significant statistical differences in grades, while Beck (2014), Hollister and Berenson (2009) and Stuber-McEwen et al (2009) do not find any differences. Recently, some studies have compared the NPR method to the RP method, for which various tools have been used.…”
Section: Monitoring Methods and Student Performancementioning
confidence: 88%
“…This study identified the likelihood of student cheating at formative vocabulary tests that were conducted before and during online remote learning. It adopted the approaches employed by previous studies: comparing students' test score results in offline and online settings (e.g., Brallier & Palm, 2015;Chuang et al, 2017;Ranger et al, 2020) and exploring students' grade patterns (Arnold, 2016). The first analysis results showed that students' test scores experienced significant increases when the tests were moved to online remote settings in five courses.…”
Section: Discussionmentioning
confidence: 99%
“…When online remote examinations are not proctored, students are more likely to cheat (Harmon & Lambrinos, 2008). It has been recognized that students perform much better on unproctored online remote tests than on proctored classroom assessments, raising the possibility of cheating (Brallier & Palm, 2015;Waluyo & Tuan, 2021). Thus, to combat academic dishonesty in online testing, previous research has emphasized the importance of 1) tightening the proctoring process using webcam recording software, which can be useful during tests and for post-test evaluation (Dendir & Maxwell, 2020), and 2) using paraphrased test questions whose answers are not readily available on the internet (Golden & Kohlbeck, 2020).…”
Section: Literature Review Cheating Practices In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation